Knowledge of and experience with transgender players among soccer team staff: a cross-sectional questionnaire design - Sadamasu, A.; Yamaguchi, S.; Akagi, R.; Sasho, T.; Morikawa, T.; Ohtori, S. (The Physician and Sportsmedicine, 2021)
Objectives Transgender issues have become increasingly prominent in sports. However, knowledge of and experience with supporting transgender players across soccer team staff remain unclear. The objectives of this questionnaire-based study were to 1) clarify staff knowledge of transgender-related terminology; and 2) explore soccer team staff`s awareness and experience with supporting transgender players.